Comparing the Effectiveness of Metacognitive Therapy and Cognitive Behavioral Therapy in Improving Binge-Eating Symptoms and Metacognitive Beliefs among Individuals with Binge-Eating Disorder - Masoumi , Roya; Davoodi, Azam; Albehbahani, Marjan; Fath, Najmeh (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: This study aimed to compare the effectiveness of metacognitive therapy and cognitive behavioral therapy in reducing binge-eating symptoms and dysfunctional metacognitive beliefs among individuals with binge-eating disorder. Methods and Materials: This quasi-experimental study employed a pretest–posttest design with a two-month follow-up and two intervention groups. The statistical population comprised all individuals with binge-eating disorder who attended the Tehran Binge Eating Association in 2025. Thirty eligible participants were selected through purposive sampling and randomly assigned to either a metacognitive therapy group or a cognitive behavioral therapy group, with 15 participants in each group. Both groups received 12 group-therapy sessions. Data were collected using the Binge Eating Scale developed by Gormally et al. (1982) and the Metacognitions Questionnaire developed by Wells and Cartwright-Hatton (2004). After removing two outlier scores, data from 28 participants were analyzed using analysis of covariance in SPSS version 27. Findings: Metacognitive therapy produced a significantly greater reduction in binge-eating symptoms than cognitive behavioral therapy at posttest, and this superiority was maintained at the two-month follow-up (p < .001). Metacognitive therapy also resulted in a significantly greater reduction in the total score of dysfunctional metacognitive beliefs at posttest; however, the between-group difference was not significant at follow-up. Component-level analyses indicated that metacognitive therapy was significantly more effective in reducing positive beliefs about worry, the need to control thoughts, cognitive confidence, and cognitive self-consciousness at both posttest and follow-up (p < .001). Nevertheless, no significant difference was observed between the two treatments in negative beliefs concerning the uncontrollability and danger of thoughts (p > .05). Conclusion: Metacognitive therapy appears to be more effective than cognitive behavioral therapy in reducing binge-eating symptoms and modifying several dimensions of dysfunctional metacognitive beliefs in individuals with binge-eating disorder. However, booster sessions and longer follow-up periods may be necessary to consolidate changes in overall metacognitive beliefs.